PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. KAWASAN INDUSTRI MODERN (PERSERO) MEDAN - Kepler Sinaga; Putra Axido Sitinjak (LPPM Universitas HKBP Nommensen, 2021)
This study aims to determine the magnitude of the effect of education and training on employee performance at PT. Modern Industrial Area (PERSERO) Medan. The research approach used is a quantitative approach with causal associative methods. The population in this study were all employees of PT.Kawasan Industri Medan who had attended education and training, totaling 95 people. The sampling technique used purposive sampling using the Slovin formula, therefore the number of samples taken was 49 people.The results of the study indicate that: (1) There is a positive and significant influence on the education variable (X1) on the performance of employees (Y) of PT. Medan Industrial Estate. This can be seen from the test results obtained a significant value of 0.000 <0.05 or t count 2.441 > from t table 1.679 (α = 0.05/2, n-k-1). (2) There is a positive and significant effect on the training variable (X2) on the performance of employees (Y) of PT. Medan Industrial Estate. This can be seen from the test results obtained a significant value of 0.000 <0.05 or t count 4.267 > from t table 1.679 (α = 0.05/2, n-k-1). (3) There is a simultaneous positive and significant effect on the variables of education (X1) and training (X2) on the performance of employees (Y) of PT. Medan Industrial Estate. This can be seen from the test results obtained significant values ​​X1 and X2 0.000 <0.05 and f arithmetic value 5.552 > from f table 1.679 (α = k, n-k). 3.09. So for that, it is recommended to PT. Medan Industrial Estate to continue to improve education and training for employees so that employee performance can also increase.